Integrative emotion regulation predicts adolescents' prosocial behavior through the mediation of empathy. (August 2017) - Benita, Moti; Levkovitz, Tal; Roth, Guy
Abstract: The ability to regulate emotion plays a key role in the development of prosocial behavior. This study uses the self-determination theory conceptualization of emotion regulation to explore whether children's emotion regulation styles differentially predict their prosocial behavior in class. For the study, 240 sixth and seventh grade Israeli students and their teachers responded to self-report measures. The results of structural equation modeling showed integrative emotion regulation predicts student prosocial behavior, both directly and through the mediation of empathy towards classmates. These findings suggest integrative emotion regulation can play an important role in promoting children's psychosocial adjustment in class. Highlights: Emotion regulation is important for the developments of prosocial behavior. SDT regards integration of emotions as an adaptive form of emotion regulation. Integrative regulation is the most salient predictor of prosocial behavior. Integrative regulation is the most salient predictor of empathy. Integrative regulation predicts prosocial behavior through empathy.